Migration and the church in East Asia - Woods, Paul, 1966- (Regnum, 2020)
The Asian church has begun to respond and reach out to migrants. However, this concern for the other is patchy and lacks robust theological foundations. This work is an adaptation of the author's major study, Theologising Migration: Otherness and Liminality in East Asia, using otherness and liminality as lenses to examine the scripture in order to understand God's heart for migrants and the responsibility of His people towards them. It ends with some pointers towards concrete action by the church.